Medication Adherence and its Determinants among Type 2 Diabetic Patient in Tertiary Care Hospital - Pammi Shah; Nyamika K.C; Kabita Dhami; Nisha Kumari Shah; Mamta K.c; Khushi Pokhrel (Journal of Nobel Medical College, 2024)
Background: Diabetes mellitus imposes vast social, health, and economic impacts on individuals and countries in the long term.Inadequate medication adherence is a major factor leading to poor and suboptimal glycemic control among patients with DM, which catalyzes the magnitude of this problem and leads to the development of diabetic-related complications.